Oxidation behavior of Cr–Mn–Si alloyed steel by mold flux melt in high temperatures - Fengkang Wang; Wanlin Wang; Jiang Du; Li Zhang; IL Sohn; Jie Zeng (Journal of Materials Research and Technology, 2024)
The oxidation behavior of a medium carbon Cr–Mn–Si alloyed steel was investigated under a mold flux melt environment exposed to different high temperatures of 1175–1425 °C, and holding time of 5–85 min. The results showed that the thicknesses of oxide layers contained Cr–Mn–Si oxide particles significantly increased from 10 to 183 μm with the increasing of oxidation temperature and holding time. The selective oxidation of Cr, Mn and Si elements in the grain boundaries is caused by the diffusion of free oxygen (O2−) migrating from mold flux to steel matrix, which leads to the growth of oxide layer thicknesses. Moreover, the oxidation rate constant (kp) of the Cr–Mn–Si alloyed steel was revealed under the mold flux environment at the temperatures of 1175–1375 °C. In addition, it was found that the growth kinetics of oxide particles in the oxide layer consists of a rapid growth stage and a slow-steady growth stage, and the growth of oxide particles is co-controlled by the diffusion of O2− within the steel matrix and the competing oxidation reactions involving Fe, Cr, Mn, and Si elements.